Lithium ion secondary battery and preparation method thereof, battery module, battery pack and device

By adding lithium-rich metal oxides to the positive electrode sheet of lithium-ion secondary battery and controlling the proportion of fluorine elements in the electrolyte, the safety hazards and insufficient energy density of the battery under high temperature conditions are solved, and a higher cycle life and safety performance are achieved.

CN115803932BActive Publication Date: 2025-03-14CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080102737.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-24
Publication Date
2025-03-14
Estimated Expiration
2040-12-24

AI Technical Summary

Technical Problem

Existing lithium-ion secondary batteries have safety hazards under high temperature conditions, and their energy density and cycle life are insufficient, making it difficult to meet the needs of large devices.

Method used

By adding lithium-rich metal oxides to the positive electrode sheet as the positive electrode lithium supplement material, and controlling the proportion of the total mass of fluorine element in the anions of the electrolyte lithium salt in the electrolyte is within an appropriate range to reduce metal ion dissolution and side reactions.

Benefits of technology

It improves the battery's high-temperature cycle life and high-temperature storage life, enhances the battery's high-temperature safety performance, and improves the energy density and first-time discharge capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115803932B_ABST
    Figure CN115803932B_ABST
Patent Text Reader

Abstract

The present application discloses a lithium-ion secondary battery and a preparation method thereof, a battery module, a battery pack and a device. The lithium-ion secondary battery includes a positive electrode plate, a negative electrode plate and an electrolyte, wherein the positive electrode plate includes a positive electrode active material and a positive electrode lithium supplement material, the positive electrode lithium supplement material includes a lithium-rich metal oxide, and the lithium-rich metal oxide contains one or more elements of Ni, Co, Fe, Mn and Cu; the electrolyte includes an electrolyte lithium salt and a solvent, and the total mass of the fluorine element in the anion of the electrolyte lithium salt accounts for ε<14% of the total mass of the electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a lithium-ion secondary battery and a preparation method thereof, a battery module, a battery pack and a device. Background Art

[0002] Lithium-ion secondary batteries are rechargeable batteries that can be used again after being discharged by activating the active material through charging. Specifically, lithium-ion secondary batteries rely on the reciprocating insertion and extraction of lithium ions between the positive and negative electrodes to achieve charging and discharging. Due to their outstanding features such as high energy density, long cycle life, no pollution, and no memory effect, lithium-ion secondary batteries are widely used in various electronic products and are rapidly popularized in large-scale devices such as electric vehicles and energy storage systems.

[0003] In large-scale devices, multiple lithium-ion secondary batteries are usually combined into battery modules or battery packs to meet the demand for high capacity. At this time, if any one or several lithium-ion secondary batteries experience thermal runaway, it will bring major safety hazards. In order to promote the further development of electric vehicles and energy storage systems, it is necessary to improve the safety performance of lithium-ion secondary batteries while having a higher energy density. Summary of the invention

[0004] In a first aspect, the present application provides a lithium-ion secondary battery, comprising a positive electrode plate, a negative electrode plate and an electrolyte, wherein the positive electrode plate comprises a positive electrode active material and a positive electrode lithium supplement material, the positive electrode lithium supplement material comprises a lithium-rich metal oxide, and the lithium-rich metal oxide contains one or more elements of Ni, Co, Fe, Mn, and Cu; the electrolyte comprises an electrolyte lithium salt and a solvent, and the total mass of the fluorine element in the anion of the electrolyte lithium salt accounts for ε<14% of the total mass of the electrolyte. Optionally, 1.5%≤ε≤9.5%.

[0005] Lithium-rich metal oxides contain one or more of Ni, Co, Fe, Mn, and Cu, which can increase their own lithium insertion capacity, thereby releasing more active lithium during battery charging, thereby more effectively compensating for the irreversible loss of lithium, thereby enabling the battery to have a higher high-temperature cycle life or high-temperature storage life. In addition, batteries with active materials with high coulombic efficiency such as lithium iron phosphate in the positive electrode can also have an improved first discharge capacity.

[0006] Adding positive electrode lithium supplement materials to the positive electrode plate and making the electrolyte satisfy the ratio of the total mass of fluorine elements in the anions of the electrolyte lithium salt to the total mass of the electrolyte within an appropriate range can significantly reduce the dissolution of metal ions. Therefore, while increasing the volume energy density of the battery, the self-discharge rate of the battery is kept low, thereby further improving the discharge capacity of the battery. In particular, the amount of metal deposition on the surface of the negative electrode is significantly reduced, which not only further reduces the side reactions of the electrolyte and reduces the gas production, but also reduces the risk of the deposited metal piercing the isolation membrane during the heating process of the battery, causing a short circuit in the battery, thereby effectively improving the high-temperature safety performance of the battery.

[0007] In any embodiment of the present application, the total mass of fluorine in the anions of the electrolyte lithium salt relative to the total mass of the electrolyte is 2%≤ε≤9.3%. Optionally, ε is 2.5% to 9.2%. The total mass of fluorine in the anions of the electrolyte lithium salt relative to the total mass of the electrolyte is within the above range, which can further reduce the dissolution of metal ions and is conducive to the electrolyte obtaining a higher ionic conductivity, thereby enabling the battery to obtain a higher high-temperature safety performance while also having a higher high-temperature cycle performance and high-temperature storage performance.

[0008] In any embodiment of the present application, the lithium-rich metal oxide can be selected from Li x M 1 O 0.5(2-x) 、Li2M 2 O3、Li2M 3 O4、Li3M 4 O4、Li5M 5 O4、Li5M 6 O6, one or more, where x≥1, M 1 One or more selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, M 2 One or more selected from Ni, Co, Fe, Mn, Sn, Cr, M 3 One or more selected from Ni, Co, Fe, Mn, Sn, Cr, V, Nb, M 4 One or more selected from Ni, Co, Fe, Mn, Sn, Cr, V, Mo, Nb, M 5 One or more selected from Ni, Co, Fe, Mn, Sn, Cr, Mo, M 6 One or more selected from Ni, Co, and Mn, M 1 、M 2 、M 3 、M 4 、M 5 、M 6 The valence state of each element in the ionomer is lower than its own highest oxidation state.

[0009] In any embodiment of the present application, the lithium-rich metal oxide may include Li2MnO2, Li5FeO4, Li6CoO4, Li2NiO2, Li2Cu x1 Ni 1-x1-y1 M y1 One or more of O2, and optionally one or more of Li3VO4, Li3NbO4, wherein 0<x1≤1, 0≤y1<0.1, and M is selected from one or more of Zn, Sn, Mg, Fe and Mn. Optionally, 0.2≤x1≤0.8, or 0.4≤x1≤0.6. The above-mentioned lithium-rich metal oxide has a high lithium desorption capacity and a suitable first lithium desorption voltage, thereby having a good lithium replenishment effect, thereby helping to improve the battery energy density. In addition, appropriate lithium-rich metal oxides can also help to improve the high temperature cycle life or high temperature storage performance of the battery.

[0010] In any embodiment of the present application, the lithium-rich metal oxide may contain free lithium, and the free lithium includes one or more of LiOH, LiHCO3 and Li2CO3, and the mass proportion of free lithium in the lithium-rich metal oxide is ω≤5wt%. Optionally, ω≤3wt%. Further optionally, 0.3wt%≤ω≤0.7wt%. The free lithium in the lithium-rich metal oxide can consume HF, thereby further reducing the dissolution of metal ions. The content of free lithium within an appropriate range can not only reduce the electrochemically inert material in the pole piece, so that the battery has a higher energy density, but also reduce the decomposition and gas production of free lithium, so that the battery has higher high-temperature cycle performance and high-temperature storage performance.

[0011] In any embodiment of the present application, at least a portion of the outer surface of the lithium-rich metal oxide may have a coating layer, which includes one or more of metal fluoride, oxide, metal phosphate, carbon material, and conductive polymer.

[0012] In any embodiment of the present application, the metal fluoride may be selected from AlF3. The oxide may be selected from one or more of V2O5, Al2O3, ZrO2, TiO2, ZnO, SiO2, and B2O3. The metal phosphate may be selected from one or more of AlPO4, FePO4, Co3(PO4)2, and Ni3(PO4)2. The coating layer can isolate the lithium-rich metal oxide from the external environment, thereby effectively alleviating the capacity loss of the lithium-rich metal oxide itself due to water absorption or the side reactions in the battery, and can reduce the dissolution of metal ions. Therefore, the lithium-rich metal oxide modified by the coating layer can further improve the high-temperature safety performance of the battery, and can improve the high-temperature cycle performance and high-temperature storage performance.

[0013] In any embodiment of the present application, the electrolyte lithium salt may include one or more selected from lithium difluorooxalatoborate (LiDFOB), lithium bisoxalatoborate (LiBOB), lithium difluorophosphate (LiDFP), lithium difluorobisoxalatophosphate (LiDFOP), lithium tetrafluorophosphate (LiTFOP), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO3), bis(trifluoromethylsulfonyl)methyl lithium (LiCH(CF3SO2)2), tris(trifluoromethylsulfonyl)methyl lithium (LiC(CF3SO2)3), and optionally includes lithium hexafluorophosphate (LiPF6). The use of a suitable electrolyte lithium salt is conducive to making the fluorine content of the electrolyte within the required range, and at the same time, the electrolyte can also have higher thermal stability and electrochemical stability, thereby further improving the high temperature safety performance of the battery, and can improve the high temperature cycle life and high temperature storage performance.

[0014] In any embodiment of the present application, the electrolyte lithium salt may include one or more of lithium bis(oxalatoborate) (LiBOB), lithium difluorobis(oxalatophosphate) (LiDFOP), and lithium bis(fluorosulfonyl)imide (LiFSI).

[0015] In any embodiment of the present application, the concentration of the electrolyte lithium salt in the electrolyte is 0.7 mol / L to 4 mol / L, and optionally 0.7 mol / L to 3 mol / L. The appropriate content of the electrolyte lithium salt can enable the electrolyte to obtain a higher ionic conductivity, thereby improving the battery energy density and cycle performance.

[0016] In any embodiment of the present application, the concentration of LiPF6 in the electrolyte is ≤0.4 mol / L. Since LiPF6 is easily ionized in the electrolyte to form F - , PF5, PF6 - Fluorine-containing particles such as LiPF6 can easily cause metal ions to dissolve in the electrolyte. The low content of LiPF6 in the electrolyte is conducive to reducing the above problems. In addition, controlling the concentration of LiPF6 in the electrolyte within the above range can further control the ε value of the electrolyte, thereby further reducing the self-discharge rate.

[0017] In any embodiment of the present application, the positive electrode active material can be selected from Li z CoO2、Li z NiO2、Li z MnO2、Li z Mn2O4、Li z Ni a Co b Mn c M' d O2、Li zNi 1-u Co u O2、Li z Co 1-u Mn u O2、Li z Ni 1-u Mn u O2、Li z Ni α Co β Mn γ O4、Li z Mn 2-η N i ηO4、Li z Mn 2-η Co η O4、Li z FePO4、Li z CoPO4、Li z MnPO4, and one or more of their modified materials, wherein M' is selected from one or more of Al, Mo, Nd, and Zn, z independently satisfies 0.5≤z≤1.3, 0<a<1, 0<b<1, 0<c<1, 0≤d<1, a+b+c+d=1, u independently satisfies 0<u<1, 0<α<2, 0<β<2, 0<γ<2, α+β+γ=2, and η independently satisfies 0<η<2.

[0018] In any embodiment of the present application, the positive electrode active material may include Li z One or more of FePO4 and its modified materials, wherein 0.5≤z≤1.3. Optionally, 0.9≤z≤1.2, or z=1. Using Li z FePO4 and its modified materials are beneficial for batteries to obtain higher high-temperature safety performance.

[0019] The positive electrode active material is contained in a positive electrode active material layer of the positive electrode sheet. In some embodiments, the surface density of the positive electrode active material layer is ≥18 mg / cm 2 , further optionally 18 mg / cm 2 ~21mg / cm 2 Designing a larger positive electrode active material layer density can increase the energy density of the battery.

[0020] In any embodiment of the present application, the positive electrode active material may include Li z Ni a Co b Mn c M' dOne or more of O2 and its modified materials, wherein 0.5≤z≤1.3, 0.5≤a<1, 0<b≤0.2, 0<c≤0.3, 0≤d<1, and M' is selected from one or more of Al, Mo, Nd, and Zn. The positive electrode active material can enable the battery to obtain a higher energy density.

[0021] In any embodiment of the present application, the positive electrode plate includes a positive current collector and a positive active material layer disposed on the positive current collector, wherein the positive active material layer contains positive active materials; wherein the positive lithium supplement material is uniformly distributed in the positive active material layer, and / or the positive lithium supplement material is disposed between the positive current collector and the positive active material layer in the form of a lithium supplement film layer, and / or the positive lithium supplement material is disposed on the surface of the positive active material layer away from the positive current collector in the form of a lithium supplement film layer. The use of a lithium supplement film layer can further improve the safety performance of the battery.

[0022] In any embodiment of the present application, on at least one side of the positive current collector, the mass ratio of the positive electrode active material to the positive electrode lithium supplement material is 99.9:0.1 to 85:15, optionally 98.5:1.5 to 93:7, and further optionally 98:2 to 95:5. In the positive electrode sheet, the ratio of the positive electrode active material to the positive electrode lithium supplement material is within an appropriate range, which can provide sufficient lithium, thereby helping to improve the high temperature cycle performance and high temperature storage performance of the battery, and also improve the overcharge performance of the battery. The positive electrode sheet can also have a higher proportion of active materials, which helps to make the battery have a higher energy density.

[0023] The second aspect of the present application provides a method for preparing a lithium-ion secondary battery, comprising the following steps: providing a positive electrode plate, wherein the positive electrode plate comprises a positive electrode active material and a positive electrode lithium supplement material, wherein the positive electrode lithium supplement material comprises a lithium-rich metal oxide, wherein the lithium-rich metal oxide contains one or more elements of Ni, Co, Fe, Mn, and Cu; providing an electrolyte, wherein the electrolyte comprises an electrolyte lithium salt and a solvent, and the total mass of the fluorine element in the anions of the electrolyte lithium salt accounts for ε<14% of the total mass of the electrolyte, and optionally, 1.5%≤ε≤9.5%; assembling the positive electrode plate, the negative electrode plate, and the electrolyte to obtain a lithium-ion secondary battery.

[0024] A third aspect of the present application provides a battery module, comprising the lithium-ion secondary battery according to the present application.

[0025] A fourth aspect of the present application provides a battery pack, comprising a battery module according to the present application.

[0026] A fifth aspect of the present application provides a device comprising at least one of the lithium-ion secondary battery, battery module, or battery pack according to the present application.

[0027] The battery module, battery pack and device provided in the present application include the lithium-ion secondary battery according to the present application, and thus can have corresponding beneficial effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of one embodiment of the secondary battery of the present application.

[0029] Figure 2 It is an exploded schematic diagram of one embodiment of the secondary battery of the present application.

[0030] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.

[0031] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.

[0032] Figure 5 yes Figure 4 Exploded diagram of .

[0033] Figure 6 This is a schematic diagram of an embodiment of a device using a secondary battery of the present application as a power source.

[0034] In this application, the drawings are not drawn to scale. DETAILED DESCRIPTION

[0035] In order to make the invention purpose, technical scheme and beneficial technical effect of the present application clearer, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the embodiments described in this specification are only for explaining the present application, not for limiting the present application.

[0036] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.

[0037] In the description of this article, it should be noted that, unless otherwise specified, "above" and "below" are inclusive of the number, and "several" in "one or several" means two or more.

[0038] The above-mentioned summary of the invention of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.

[0039] Generally, lithium-ion secondary batteries include a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the battery charging and discharging process, active ions (lithium ions) are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing lithium ions to pass through. The electrolyte is between the positive electrode sheet and the negative electrode sheet, mainly to conduct ions.

[0040] During the first charge of the battery, lithium ions are released from the positive electrode active material, conducted through the electrolyte, and embedded in the negative electrode active material. In this process, some lithium ions participate in the reaction of forming a solid electrolyte interface (SEI) film on the surface of the negative electrode active material, resulting in loss of active lithium. In addition, during the subsequent cycle charge and discharge process and storage process of the battery, the repair and growth of the SEI film, as well as the side reactions of the electrolyte on the surface of the lithium-embedded negative electrode may also occur, which will irreversibly consume lithium ions. The consumption of active lithium will lead to lower cycle performance and / or storage performance of the battery. At the same time, the lithium consumption reaction will also increase the gas production inside the battery, resulting in poor safety performance. The above effects are more serious under high temperature conditions (for example, above 45°C, such as 45°C to 80°C or 45°C to 60°C, etc.).

[0041] In addition, the loss of active lithium to form the SEI film during the first charge will also result in a lower first discharge capacity, which is not conducive to improving the battery energy density.

[0042] The pre-lithium replenishment scheme can provide additional active lithium, thereby compensating for the loss of active lithium. The means of pre-lithium replenishment mainly include negative electrode lithium replenishment and positive electrode lithium replenishment. Negative electrode lithium replenishment usually uses metal lithium powder or lithium belt to pre-lithiate the negative electrode active material. However, due to the high activity of metallic lithium, it has high requirements for the environment and equipment, which makes the process of negative electrode lithium replenishment complicated and costly, which is not conducive to large-scale application. The positive electrode lithium replenishment scheme can be to add lithium-rich compounds to the positive electrode as lithium replenishment materials, avoiding the use of metallic lithium. The lithium-rich compound releases lithium when the battery is charged, which can compensate for the irreversible loss of active lithium during the formation of SEI film during the first charging of the battery and the subsequent cycling process and storage process, thereby improving the discharge capacity retention rate of the battery after cycling and / or storage. However, the inventors found that the battery using positive electrode lithium replenishment still has the problem of low high temperature safety performance.

[0043] In order to make the battery have both high energy density and high temperature safety performance, the inventors have further conducted a lot of research and found that the above invention purpose can be achieved by adding a suitable positive electrode lithium supplement material to the positive electrode plate and making the total mass of fluorine in the anions of the electrolyte lithium salt in the electrolyte less than 14% of the total mass of the electrolyte. The total mass of fluorine in the anions of the electrolyte lithium salt relative to the total mass of the electrolyte can be measured by ion chromatography.

[0044] Therefore, the first aspect of the present application provides a lithium-ion secondary battery. In the lithium-ion secondary battery, the positive electrode plate includes a positive electrode active material and a positive electrode lithium supplement material, the positive electrode lithium supplement material includes a lithium-rich metal oxide, and the lithium-rich metal oxide contains one or more elements of Ni, Co, Fe, Mn, and Cu; and the electrolyte includes an electrolyte lithium salt and a solvent, and the total mass of the fluorine element in the anion of the electrolyte lithium salt accounts for ε<14% of the total mass of the electrolyte.

[0045] The inventors have found that lithium-rich metal oxides contain one or more of Ni, Co, Fe, Mn, and Cu, which can increase their own lithium insertion capacity. Accordingly, lithium-rich metal oxides have a higher lithium removal capacity and can release more active lithium during battery charging, thereby more effectively compensating for the irreversible loss of lithium, thereby enabling the battery to have a higher cycle life or storage life under high temperature conditions. In addition, batteries with higher positive electrode first efficiency, such as lithium iron phosphate / graphite batteries, can also have an improved first discharge capacity.

[0046] The explanation of the effect of the present application is not expected to be subject to any theoretical limitations. The lithium-rich metal oxide will undergo drastic changes in the lattice during the delithiation process. At this time, the electrolyte satisfies the total mass of the fluorine element in the anion of the electrolyte lithium salt relative to the total mass of the electrolyte. The proportion is within an appropriate range, which can effectively alleviate the problem of metal ion dissolution. The amount of metal ion dissolution is significantly reduced, which can reduce the amount of metal deposition on the surface of the negative electrode, thereby further reducing not only the side reactions of the electrolyte and the gas production, but also the risk of the deposited metal piercing the isolation membrane during the heating process of the battery to cause a short circuit in the battery, thereby further improving the high temperature safety performance of the battery.

[0047] In addition, since the metal ions dissolved from lithium-rich metal oxides are greatly reduced, the shuttling effect of metal ions or the self-discharge of the battery caused by deposition on the negative electrode surface can be significantly reduced, thereby improving the capacity of the battery and further improving the discharge capacity of the battery. Moreover, the metal ion reduction reaction occurring on the negative electrode surface is reduced, thereby reducing the damage to the SEI film, thereby reducing the consumption of electrolyte and active lithium caused by the continuous repair of the SEI film, thereby enabling the battery to have a higher discharge capacity retention rate during the cycle or storage process at high temperature. Therefore, the high-temperature cycle performance or high-temperature storage performance of the battery is further improved.

[0048] In some embodiments, in the electrolyte, the total mass of the fluorine element in the anion of the electrolyte lithium salt relative to the total mass of the electrolyte is ≤13.8%, ≤13.5%, ≤13%, ≤12.5%, ≤12%, ≤11.5%, ≤11%, ≤10.5%, ≤10%, ≤9.5%, ≤9.3%, ≤9%, ≤8.5%, ≤8%, ≤7.5%, ≤7%, ≤6.5%, ≤6%, ≤5.5%, ≤5%, ≤4.5%, ≤4%, ≤3.5%, ≤3%, or ≤2.5%. The ε value of the electrolyte is within an appropriate range, which can further reduce the dissolution of metal ions and is more conducive to improving the high temperature safety performance of the battery. In addition, the high temperature storage performance or high temperature cycle performance of the battery can also be further improved.

[0049] In some embodiments, the ε of the electrolyte is ≥0%, ≥0.5%, ≥0.8%, ≥1%, ≥1.1%, ≥1.2%, ≥1.3%, ≥1.4%, ≥1.5%, ≥1.6%, ≥1.8%, ≥2%, ≥2.3%, or ≥2.5%. The electrolyte contains an appropriate amount of fluorine, which is beneficial for the electrolyte to obtain a higher ionic conductivity, thereby facilitating the improvement of the first discharge capacity, high temperature cycle performance and high temperature storage performance of the battery. In addition, the battery can also have higher power performance.

[0050] In some embodiments, the ε of the electrolyte is 0-10%, 0-9.3%, 1%-9.5%, 1.5%-9.5%, 2%-9.3%, 2.5%-9.2%, 0.5%-8.5%, 1%-8%, 1%-7.5%, 1.2%-7%, 1.3%-6.5%, 1.5%-5%, or 2%-5%, etc.

[0051] [Positive electrode]

[0052] The positive electrode sheet generally includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector. As an example, the positive current collector has two surfaces opposite to each other in its thickness direction, and the positive active material layer is disposed on either or both of the two surfaces of the positive current collector.

[0053] The positive electrode current collector may be a metal foil or a composite current collector (a metal material may be disposed on a polymer material layer to form a composite current collector). As an example, the positive electrode current collector may be an aluminum foil.

[0054] The positive electrode active material layer includes a positive electrode active material. The positive electrode active material can be a material known in the art for a positive electrode of a lithium ion secondary battery and capable of reversibly inserting and extracting lithium ions. In some embodiments, the positive electrode active material can be selected from Li z CoO2、Li zNiO2、Li z MnO2、Li z Mn2O4、Li z Ni a Co b Mn c M' d O2、Li z Ni 1-u Cc u O2、Li z Co 1-u Mn u O2、Li z Ni 1-u Mn u O2、Li z Ni α Co β Mn γ O4、Li z Mn 2-η Ni η O4、Li z Mn 2-η Co η O4、Li z FePO4、Li z CoPO4、Li z MnPO4, and one or more of their modified materials, wherein M' is selected from one or more of Al, Mo, Nd, and Zn, z independently satisfies 0.5≤z≤1.3, 0<a<1, 0<b<1, 0<c<1, 0≤d<1, a+b+c+d=1, u independently satisfies 0<u<1, 0<α<2, 0<β<2, 0<γ<2, α+β+γ=2, and η independently satisfies 0<η<2.

[0055] Herein, the modification in the modified material may be one or more of doping modification and coating modification.

[0056] In some embodiments, the positive electrode active material may include Li z One or more of FePO4 and its modified materials, wherein 0.5≤z≤1.3. Optionally, 0.8≤z≤1.3, 0.9≤z≤1.2, or 0.95≤z≤1.1. In some embodiments, z=1. Li z FePO4 and its modified materials have high thermal stability, which is conducive to the battery to obtain higher high-temperature safety performance. In addition, the battery can also have a longer high-temperature cycle life and higher high-temperature storage performance.

[0057] In some embodiments, Li zThe modified material of FePO4 can be a material in which Fe is partially replaced by a metal element other than Fe and having an atomic radius close to that of Fe, such as Sc, V, Cr, Mn, Ti, Al, Co, Ni, Cu, Zn, etc. z Examples of modified materials for FePO4 include Li z Fe 1-k Me k PO4, wherein Me is selected from one or more of Sc, V, Cr, Mn, Ti, Al, Co, Ni, Cu, and Zn, and 0<k≤0.5. Optionally, 0.01≤k≤0.2. Optionally, Me is selected from one or more of Mn, Ti, Al, Ni, Cu, and Zn.

[0058] The inventors further discovered that when the positive electrode active material includes Li z One or more of FePO4 and its modified materials can further improve the performance of the battery if the positive electrode plate meets one or more of the following conditions at the same time.

[0059] In some embodiments, the surface density of the positive electrode active material layer is ≥18 mg / cm 2 Optionally, the surface density of the positive electrode active material layer is 18 mg / cm 2 ~26mg / cm 2 , further optionally 18 mg / cm 2 ~25mg / cm 2 , 18mg / cm 2 ~23mg / cm 2 , 18mg / cm 2 ~21mg / cm 2 , 19mg / cm 2 ~22mg / cm 2 , or 20mg / cm 2 ~25mg / cm 2 In the lithium-ion secondary battery of the present application, a larger positive electrode active material layer density can be designed, thereby further improving the energy density of the battery.

[0060] In these embodiments, the compaction density of the positive electrode active material layer may be 2.0 g / cm 3 ~2.6g / cm 3 , for example 2.2 g / cm 3 ~2.4g / cm 3 The compaction density of the positive electrode active material layer is within an appropriate range, which can ensure good electron transmission performance of the positive electrode sheet and at the same time have a porosity suitable for electrolyte infiltration, thereby facilitating the battery to obtain higher cycle performance.

[0061] In some embodiments, the positive electrode active material may include Li z Ni a Co b Mn c M' d O2 and one or more of its modified materials, wherein 0.5≤z≤1.3, 0.5≤a<1, 0<b≤0.2, 0<c≤0.3, 0≤d<1, M' is selected from one or more of Al, Mo, Nd, Zn. Optionally, 0.8≤z≤1.2. Optionally, 0.5≤a≤0.9, 0.6≤a≤0.85, or 0.65≤a≤0.8. As an example, the positive electrode active material can be selected from LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2, modified materials of the above materials, etc. The use of the above positive electrode active materials can enable the battery to obtain a higher energy density.

[0062] In some embodiments, the lithium-rich metal oxide may be selected from Li x M 1 O 0.5(2+x) 、Li2M 2 O3、Li2M 3 O4、Li3M 4 O4、Li5M 5 O4、Li5M 6 O6, one or more, where x≥1, M 1 One or more selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, M 2 One or more selected from Ni, Co, Fe, Mn, Sn, Cr, M 3 One or more selected from Ni, Co, Fe, Mn, Sn, Cr, V, Nb, M 4 One or more selected from Ni, Co, Fe, Mn, Sn, Cr, V, Mo, Nb, M 5 One or more selected from Ni, Co, Fe, Mn, Sn, Cr, Mo, M 6 One or more selected from Ni, Co, and Mn, M 1 、M 2 、M 3 、M 4 、M 5 、M 6The valence state of each element in the ionomer is lower than its own highest oxidation state.

[0063] In some embodiments, the lithium-rich metal oxide may include Li2MnO2, Li5FeO4, Li6CoO4, Li2NiO2, Li2Cu x1 Ni 1-x1-y1 M y1 O2, and optionally include one or more of Li3VO4, Li3NbO4. Optionally, the lithium-rich metal oxide may include Li2MnO2, Li5FeO4, Li6CoO4, Li2NiO2, Li2Cu x1 Ni 1-x1-y1 M y1 O2. Further optionally, the lithium-rich metal oxide may include Li5FeO4, Li6CoO4, Li2Cu x1 Ni 1-x1-y1 M y1 One or more of O2. Li2Cu x1 Ni 1-x1-y1 M y1 In O2, 0<x1≤1, 0≤y1<0.1, M is selected from one or more of Zn, Sn, Mg, Fe and Mn. Optionally, 0.2≤x1≤0.8, 0.2≤x1≤0.6, 0.3≤x1≤0.7, 0.3≤x1≤0.6, or 0.4≤x1≤0.6.

[0064] The lithium-rich metal oxide has a high lithium removal capacity and a suitable first lithium removal voltage, so that it can match the charging potential of the positive electrode active material, better play the lithium replenishment effect, and thus further improve the battery energy density. In addition, the appropriate lithium-rich metal oxide can also help improve the high-temperature cycle life or high-temperature storage performance.

[0065] In some embodiments, the lithium-rich metal oxide may include or be Li2Cu x1 Ni 1-x1-y1 M y1 O2. In the formula, the Ni / Cu atomic number ratio is 0.1 to 4. Optionally, the Ni / Cu atomic number ratio is 1:4 to 4:1, 1:2 to 4:1, 2:3 to 4:1, 3:7 to 7:3, 4:6 to 7:3, or 4:6 to 6:4. The use of this lithium-rich metal oxide can further improve the energy density of the battery, and can enhance the high-temperature cycle performance, high-temperature storage performance and high-temperature safety performance of the battery. The inventors also found that the use of this positive electrode lithium supplement material can further enhance the overcharge window of the battery, so that the battery can obtain a higher overcharge performance.

[0066] In some embodiments, the first lithium removal capacity of the lithium-rich metal oxide is ≥250mAh / g. Optionally, the first lithium removal capacity of the lithium-rich metal oxide is ≥300mAh / g, ≥350mAh / g, ≥400mAh / g, or ≥450mAh / g. The first lithium removal capacity of the lithium-rich metal oxide is relatively high, and it can release more active lithium when used in the battery, thereby helping to improve the energy density of the battery. Furthermore, the battery can also obtain a longer cycle life or storage life.

[0067] In some embodiments, the first delithiation platform voltage of the lithium-rich metal oxide is 2.0V to 4.5V (relative to Li / Li + Optionally, the first delithiation platform voltage of the lithium-rich metal oxide is 2.5V to 4.2V, 3V to 4.2V, 2.8V to 4V, 3.0V to 3.75V, 32V to 3.6V, or 3.4V to 4.1V (relative to Li / Li + ). Lithium-rich metal oxides have a lower lithium desorption platform voltage, which can match the lithium desorption potential of the positive electrode active material, thereby better exerting the capacity of the lithium replenishment material and the active material and improving the lithium replenishment effect.

[0068] In some embodiments, the lithium-rich metal oxide may contain free lithium, and the free lithium includes one or more of LiOH, LiHCO3, and Li2CO3. The free lithium in the lithium-rich metal oxide can consume HF, thereby further reducing the dissolution of metal ions.

[0069] In some embodiments, the mass proportion of free lithium in the lithium-rich metal oxide is ω≤5wt%. Optionally, ω≤3wt%. Further optionally, 0.1wt%≤ω≤3wt%, 0.1wt%≤ω≤2wt%, 0.2wt%≤ω≤1wt%, or 0.3wt%≤ω≤0.7wt%. The content of free lithium in the lithium-rich metal oxide is within an appropriate range, which can reduce the decomposition and gas production of free lithium and maintain a good reaction interface of the pole piece, so that the battery obtains higher high-temperature cycle performance and high-temperature storage performance. In addition, free lithium is an electrochemically inert material, and reducing the free lithium content in the positive electrode is conducive to the battery obtaining a higher energy density.

[0070] In some embodiments, at least a portion of the outer surface of the lithium-rich metal oxide has a coating. The coating may include one or more of a metal fluoride, an oxide, a metal phosphate, a carbon material, and a conductive polymer. The oxide is selected from oxides of elements from Groups IB to VIIB, Groups VIII, Group IIIA, and Group IV of the periodic table except C, or lithium composite oxides. Optionally, the coating may include one or more of a metal fluoride, an oxide, and a metal phosphate.

[0071] Lithium-rich metal oxides are usually alkaline, especially when the alkalinity is high (for example, the pH is about 12), it is easier to absorb moisture in the environment. The introduction of water into the battery by lithium-rich metal oxides will cause a series of side reactions and other problems, affecting the capacity of the battery and further improving the cycle life. The coating layer can play an isolating role, reducing the contact between the lithium-rich metal oxide and the external environment, thereby reducing the amount of water absorbed, and thus can effectively alleviate the capacity loss caused by water absorption, so that the battery can obtain a higher energy density and cycle capacity retention rate. In addition, the coating layer can also isolate the direct contact between the lithium-rich metal oxide and the electrolyte, which is conducive to further reducing the dissolution of metal ions, thereby further improving the high-temperature safety performance, high-temperature cycle performance and high-temperature storage performance of the battery.

[0072] In some embodiments, the metal fluoride may be selected from AlF3.

[0073] In some embodiments, the oxide may be selected from one or more of V2O5, Al2O3, ZrO2, TiO2, ZnO, SiO2, Co3O4, B2O3, Li2MnO3, LiAlO2, Li2TiO3, and Li2ZrO3. Alternatively, the oxide may be selected from one or more of V2O5, Al2O3, ZrO2, TiO2, ZnO, SiO2, and B2O3. Appropriate oxides can improve the stability of the coating layer and help to better isolate the lithium-rich metal oxide from the external environment or the electrolyte, thereby further reducing water absorption and metal ion dissolution.

[0074] In some embodiments, the phosphate may be selected from one or more of Li3PO4, AlPO4, FePO4, Co3(PO4)2, and Ni3(PO4)2. Alternatively, the phosphate may be selected from one or more of AlPO4, FePO4, Co3(PO4)2, and Ni3(PO4)2. Appropriate phosphates can improve the stability of the coating layer and help to better isolate the lithium-rich metal oxide from the external environment or the electrolyte, thereby further reducing water absorption and metal ion dissolution.

[0075] In some embodiments, the carbon material can be selected from one or more of graphene, carbon nanotubes, and carbon fibers.

[0076] In some embodiments, the conductive polymer can be selected from one or more of polythiophenes, polypyrroles, polyanilines, polypyridines, and modified polymers of the above materials. As an example, the modified polymer can be a polymer modified by polyethylene glycol. Examples of polythiophenes can be selected from polythiophene, poly-3,4-ethylenedioxythiophene, and the like.

[0077] In some embodiments, the coating layer comprises one or more of metal fluoride, oxide, phosphate and a conductive polymer. As an example, the coating layer comprises Al2O3 and polyethylene glycol-modified poly-3,4-ethylenedioxythiophene. As another example, the coating layer comprises Li3PO4 and polypyrrole.

[0078] In any embodiment, the coating layer may be a single layer or a multi-layer composite coating layer.

[0079] In the positive electrode sheet, the positive electrode lithium replenishing material can be loaded on the positive electrode current collector in any form that can release lithium into the electrolyte. In some embodiments, the positive electrode lithium replenishing material can be uniformly distributed in the positive electrode active material layer. That is, the positive electrode active material layer contains the positive electrode active material and the positive electrode lithium replenishing material.

[0080] In some embodiments, the positive electrode lithium replenishing material is uniformly distributed in the positive electrode active material layer, and based on the total weight of the positive electrode active material layer, the content W of the positive electrode lithium replenishing material is 0.1% to 10%. Optionally, W≥0.5%, ≥1%, ≥1.5%, ≥2%, ≥3%, or ≥4%. The content of the positive electrode lithium replenishing material in the positive electrode pole piece is within an appropriate range, which can provide sufficient lithium to make up for the active lithium consumed by the SEI film or side reactions, thereby improving the capacity retention rate of the battery during high temperature cycling or high temperature storage. The inventors also found that when the positive electrode pole piece contains an appropriate amount of positive electrode lithium replenishing material, the overcharge window of the battery can be further improved, so that the battery can obtain a higher overcharge performance. Optionally, W≤10%, ≤8%, ≤7%, or ≤6%. Making the content of the positive electrode lithium replenishing material in the positive electrode pole piece within the above range can also ensure that the positive electrode has a higher proportion of active materials, which helps the battery to obtain a higher energy density.

[0081] In some embodiments, W is 1% to 10%, 1% to 8%, 1% to 6%, 2% to 6%, 3% to 6%, 1% to 5%, 1.5% to 3%, 2% to 5%, 2% to 4%, 4% to 10%, 6% to 10%, or 8% to 10%.

[0082] In some embodiments, the positive electrode lithium replenishing material is disposed on the positive electrode current collector in the form of a lithium replenishing film layer. The lithium replenishing film layer is a thin film layer containing the positive electrode lithium replenishing material. In some embodiments, the lithium replenishing film layer can be stacked with the positive electrode active material layer and disposed on the surface of the positive electrode current collector.

[0083] As an example, the lithium replenishment film layer is disposed between the positive electrode current collector and the positive electrode active material layer. When an abnormal situation such as nail penetration occurs in the battery, the lithium replenishment film layer between the positive electrode current collector and the positive electrode active material layer can reduce the risk of the burrs of the positive electrode current collector contacting the negative electrode, and also help to improve the short-circuit resistance, thereby improving the safety performance of the battery.

[0084] As another example, the lithium replenishment film layer is disposed on the surface of the positive electrode active material layer away from the positive electrode current collector. The inventors have found that when the separator melts or punctures, causing a short circuit in the battery, the lithium replenishment film layer is disposed on the surface of the positive electrode active material layer away from the positive electrode current collector, which can improve the short circuit resistance and reduce the severity of the reaction during the short circuit, thereby further improving the high temperature safety performance of the battery. In addition, the lithium replenishment film layer is located on the outer surface of the positive electrode active material layer, which also helps to improve the overcharge performance of the battery.

[0085] In the positive electrode sheet, the lithium replenishing film layer and the positive electrode active material layer may be in contact with each other or not.

[0086] In some embodiments, on at least one side of the positive current collector, the mass ratio of the positive active material to the positive lithium supplement material is 99.9:0.1-85:15, optionally 99.5:0.5-90:10, 99.5:0.5-92:8, 99:1-89:11, 99:1-93:7, 98.5:1.5-93:7, 98.5:1.5-94:6, 98:2-94:6, 98:2-95:5, or 98:2-96:4. The content of the positive lithium supplement material in the positive electrode plate is within an appropriate range, which can provide sufficient lithium, thereby helping to improve the high temperature cycle performance and high temperature storage performance of the battery, and can also improve the overcharge performance of the battery. In addition, the positive electrode plate can also have a higher proportion of active materials, thereby helping the battery to have a higher energy density.

[0087] In the positive electrode sheet of the present application, the positive electrode active material layer and / or the lithium supplement film layer may optionally include a binder. Examples of the binder may include one or more of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).

[0088] In the positive electrode sheet of the present application, the positive electrode active material layer and / or the lithium supplement film layer may also optionally include a conductive agent. Examples of the conductive agent may include one or more of superconducting carbon, carbon black (e.g., acetylene black, Ketjen black), carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0089] It should be noted that the positive electrode active material layer and the optional lithium supplement film layer can be arranged on one side or both sides of the positive electrode current collector. The parameters of the film layer or material on either side of the positive electrode current collector satisfy this application and are considered to fall within the protection scope of this application. The compaction density, surface density, etc. of the positive electrode active material layer described in this application refer to the parameters of the positive electrode active material layer in the positive electrode sheet that has been cold pressed and can be used to assemble the battery.

[0090] In the present application, the chemical composition and the Ni / Cu atomic number ratio of the lithium-rich metal oxide can be tested by methods known in the art. For example, inductively coupled plasma emission spectroscopy. An exemplary test method for the Ni / Cu atomic number ratio of lithium-rich metal oxides is as follows: At 25°C, take 0.5g of lithium-rich metal oxide and digest it in 100mL of 0.1mol / L HCl solution for 30min. The digestion can be carried out under stirring (such as magnetic stirring, mechanical stirring or microwave stirring, etc.). The digested solution is placed in an inductively coupled plasma emission spectrometer (for example, Thermo Fisher scientificICAP7400, USA), and the content of Cu and Ni elements is selected for testing. The test conditions are: the cleaning pump is 40-60rpm (revolutions per minute), the radio frequency power is 950W-1150W, the nebulizer pressure is 24-32Psi (pounds per square inch), and the auxiliary flow rate is set to 0.5L / min. The ratio of the number of Ni / Cu atoms is calculated based on the content of Cu and Ni elements. The chemical composition of the lithium-rich metal oxide can be determined by referring to the above method.

[0091] In the present application, the mass proportion of free lithium in the lithium-rich metal oxide can be determined by methods known in the art, such as titration. The test can refer to the standard: GB / T9725-2007 General Rules for Potentiometric Titration of Chemical Reagents. The exemplary test method is as follows: Use a 905Titrando potentiometric titrator with a composite pH electrode; take 30g of lithium-rich metal oxide in an iodine volumetric bottle, add 100mL of deionized water, disperse at 25°C and 360r / min for 30min, let stand for 10min, and vacuum filter with a 0.45μm microporous filter membrane to obtain a dispersion; then titrate the dispersion with 0.05mol / L HCl solution; based on the titration amount, calculate the free lithium content and the mass proportion of free lithium in the lithium-rich metal oxide.

[0092] In this application, the surface density of the positive electrode active material layer has a well-known meaning in the art and can be tested by methods known in the art. For example, take a single-sided coated and cold-pressed positive electrode sheet (if it is a double-sided coated positive electrode sheet, the positive electrode active material layer on one side can be wiped off first), punch it into a small disc with an area of ​​S1, weigh it, and record it as M1. Then wipe off the positive electrode active material layer of the weighed positive electrode sheet, weigh the weight of the positive electrode collector, and record it as M0. The surface density of the positive electrode active material layer = (the weight of the positive electrode sheet M1-the weight of the positive electrode collector M0) / S1.

[0093] In the present application, the compaction density of the positive electrode active material layer has a well-known meaning in the art and can be tested by methods known in the art. The compaction density of the positive electrode active material layer = the surface density of the positive electrode active material layer / the thickness of the positive electrode active material layer. The thickness of the positive electrode active material layer can be tested by methods known in the art, such as a micrometer (e.g., Mitutoyo 293-100, with an accuracy of 0.1 μm).

[0094] [Electrolyte]

[0095] The electrolyte comprises an electrolyte lithium salt and a solvent, and the total mass of the fluorine element in the anion of the electrolyte lithium salt relative to the total mass of the electrolyte has a ratio ε<14%. In some embodiments, ε is ≤13.8%, ≤13.5%, ≤13%, ≤12.5%, ≤12%, ≤11.5%, ≤11%, ≤10.5%, ≤10%, ≤9.5%, ≤9.3%, ≤9%, ≤8.5%, ≤8%, ≤7.5%, ≤7%, ≤6.5%, ≤6%, ≤5.5%, ≤5%, ≤4.5%, ≤4%, ≤3.5%, ≤3%, or ≤2.5%. In some embodiments, ε is ≥0%, ≥0.5%, ≥0.8%, ≥1%, ≥1.1%, ≥1.2%, ≥1.3%, ≥1.4%, ≥1.5%, ≥1.6%, ≥1.8%, ≥2%, ≥2.3%, or ≥2.5%. Optionally, ε is 0-10%, 0-9.3%, 1%-9.5%, 1.5%-9.5%, 2%-9.3%, 2.5%-9.2%, 0.5%-8.5%, 1%-8%, 1%-7.5%, 1.2%-7%, 1.3%-6.5%, 1.5%-5%, or 2%-5%, etc.

[0096] Ion chromatography can be used to determine the proportion ε of the total mass of fluorine elements in the anions of the electrolyte lithium salt relative to the total mass of the electrolyte. An exemplary test method is as follows: an ion chromatograph (e.g., ICS-900) is used; the chromatographic column is an anion separation column (e.g., Shodex IC SI-90 4E, 4.6×250 mm); the suppressor uses an anion suppressor (e.g., ACRS 500, 4 mm); the detector uses a conductivity detector; the eluent uses an aqueous solution containing 1.8 mmol / L Na2CO3+1.8 mmol / L NaHCO3+20% acetonitrile (volume / volume), with a flow rate of 1.0 mL / min. The test can be carried out in accordance with JY / T 020-1996 "General Rules for Ion Chromatography Analysis Methods". The types of anions of all electrolyte lithium salts and their respective contents in the electrolyte are measured, and then the content of each anion is multiplied by the mass percentage of fluorine in the anion, and the sum is calculated to calculate the total mass of fluorine in the anions of the electrolyte lithium salts in the electrolyte, and then ε is calculated.

[0097] It should be noted that for the test of the electrolyte, the electrolyte sample can be directly taken for testing (before injection into the battery), or a sample can be taken from a secondary battery with a charge and discharge cycle number of less than 200 cycles for testing.

[0098] In some embodiments, the electrolyte lithium salt may be selected from a combination of LiPF6 and an organic lithium salt, LiBF4, a combination of LiBF4 and an organic lithium salt, or one or more of an organic lithium salt. Alternatively, the electrolyte lithium salt may be selected from a combination of LiBF4, LiBF4 and an organic lithium salt, or one or more of an organic lithium salt. Further optionally, the electrolyte lithium salt may be selected from an organic lithium salt.

[0099] The organic anion of the organic lithium salt may be fluorine-containing or fluorine-free. In some embodiments, the organic lithium salt may be selected from lithium difluorooxalate borate (LiDFOB), lithium bisoxalate borate (LiBOB), lithium difluorophosphate (LiDFP), lithium difluorobisoxalate phosphate (LiDFOP), lithium tetrafluorooxalate phosphate (LiTFOP), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiCF3SO3), bis(trifluoromethylsulfonyl) methyl lithium (LiCH(CF3SO2)2), tris(trifluoromethylsulfonyl) methyl lithium (LiC(CF3SO2)3). Optionally, the organic lithium salt may include one or more of LiDFOB, LiBOB, LiTFOP, LiTFSI, LiDFOP, and LiFSI. Further optionally, the organic lithium salt may include one or more of LiDFOB, LiBOB, LiTFOP, LiDFOP, and LiFSI. Further optionally, the organic lithium salt may include one or more of LiBOB, LiDFOP, and LiFSI.

[0100] The use of suitable electrolyte lithium salts is conducive to making the fluorine content of the electrolyte within the required range, and at the same time, it can also make the electrolyte have a higher ionic conductivity, thereby improving the capacity of the battery and the capacity retention rate during the cycle process, thereby further improving the initial discharge capacity and cycle life. Suitable electrolyte lithium salts can also have high thermal stability and electrochemical stability, thereby further improving the high-temperature cycle life and high-temperature storage performance of the battery, and can improve the high-temperature safety performance of the battery. Among them, the thermal diffusion performance or hot box performance of the battery is significantly improved.

[0101] In some embodiments, the concentration of the electrolyte lithium salt in the electrolyte is 0.7mol / L to 4mol / L. Optionally, the concentration of the electrolyte lithium salt in the electrolyte is 0.7mol / L to 3mol / L, 0.9mol / L to 2mol / L, 1mol / L to 1.5mol / L, 1mol / L to 4mol / L, or 2mol / L to 4mol / L. The appropriate content of the electrolyte lithium salt can enable the electrolyte to obtain a higher ionic conductivity, further improve the capacity of the positive electrode lithium supplement material, and improve the battery energy density.

[0102] In some embodiments, the electrolyte contains LiPF6, and the concentration of LiPF6 in the electrolyte is ≤0.4 mol / L. Optionally, the concentration of LiPF6 in the electrolyte is ≤0.3 mol / L, ≤0.2 mol / L, or ≤0.1 mol / L. In some embodiments, the concentration of LiPF6 in the electrolyte is 0 to 0.4 mol / L, 0.05 mol / L to 0.3 mol / L, or 0.1 mol / L to 0.2 mol / L, etc. Since LiPF6 is easily ionized in the electrolyte to form F - , PF5, PF6 - Fluorine-containing particles such as fluorine-containing particles are easy to cause metal ions to dissolve in the electrolyte. The low content of LiPF6 in the electrolyte is conducive to reducing the above problems. In addition, by controlling the concentration of LiPF6 in the electrolyte within the above range, the ε value of the electrolyte can be further controlled, thereby further reducing the self-discharge rate.

[0103] In some embodiments, the solvent of the electrolyte may include one or more of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate and methyl butyrate.

[0104] In some embodiments, the solvent includes one or more of EC and PC, and includes one or more of DEC, DMC, and EMC. As an example, the solvent includes EC, EMC, and optionally PC. Optionally, in the solvent, the volume proportion of EC is 20% to 40%, the volume proportion of PC is 0% to 20%, and the volume proportion of EMC is 60% to 80%. For example, the volume ratio of EC, PC, and EMC is 1:1:3, or 3:0:7, etc.

[0105] In some embodiments, the solvent of the electrolyte may also optionally include one or more of gamma-butyrolactone (GBL) and dimethyl methylphosphonate (DMMP), which is beneficial for reducing the density of the electrolyte, reducing the weight of the battery, and thus improving the energy density.

[0106] In some embodiments, the solvent further comprises an optional additive. The additive may be selected from additives for secondary battery electrolytes known in the art. As an example, the additive may include one or more of a first additive, a second additive, and a third additive.

[0107] Examples of the first additive may include one or more of heptamethyldisilazane (HEMDS), ethanolamine (MEA), 1,3-propanesultone (1,3-PS), and succinonitrile (SN). The use of the first additive can consume the by-product HF in the electrolyte, thereby further inhibiting the dissolution of metal ions, which helps to improve the high temperature safety performance of the battery.

[0108] Examples of the second additive may include one or more of tris(trimethylsilyl)phosphate (TMSP) and tris(trimethylsilyl)borate (TMSB). The second additive can form a protective film on the positive electrode oxidation, which can reduce the dissolution of metal ions and protect the positive electrode active material, thereby further improving the high temperature safety performance of the battery, and also improving the high temperature cycle life or high temperature storage performance.

[0109] Examples of the third additive may include one or more of polytartaric acid borate lithium salt (PLTB), polybis(trimethylolpropane) borate lithium salt (PLDB), and polypentaerythritol borate lithium salt (PLPB). The third additive has high thermal stability and helps to improve the high temperature safety performance of the battery.

[0110] [Negative electrode]

[0111] The negative electrode sheet used in conjunction with the positive electrode sheet of the present application can be selected from various conventional negative electrode sheets commonly used in the art, and its composition and preparation method are well known in the art. For example, the negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may include a negative electrode active material and optionally a binder, optionally a conductive agent and other optional additives. The negative electrode active material is, for example, a carbonaceous material such as graphite (artificial graphite or natural graphite), conductive carbon black, carbon fiber, etc., such as Si, Sn, Ge, Bi, Sn, In and other metal or semi-metal materials or their alloys, lithium-containing nitrides or lithium-containing oxides, lithium metal or lithium aluminum alloys, etc.

[0112] As an example, the conductive agent may include one or more of superconducting carbon, carbon black (e.g., acetylene black, Ketjen black, etc.), carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The binder may include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin, polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). Other optional additives include thickeners (e.g., sodium carboxymethyl cellulose CMC-Na), PTC thermistor materials, etc.

[0113] [Isolation film]

[0114] The present application may select various conventional isolation membranes commonly used in the art. In some embodiments, the isolation membrane may be selected from glass fiber, non-woven fabric, polyethylene film, polypropylene film, polyvinylidene fluoride film, and multilayer composite films of two or more thereof.

[0115] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0116] In some embodiments, the secondary battery may include an outer package, which may be used to package the electrode assembly and the electrolyte.

[0117] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0118] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0119] In some embodiments, reference Figure 2 , the outer package may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate are enclosed to form a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to needs.

[0120] In some embodiments, secondary batteries may be assembled into a battery module. The battery module may contain multiple secondary batteries, and the specific number may be adjusted according to the application and capacity of the battery module.

[0121] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0122] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0123] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0124] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0125] Preparation method

[0126] The present application also provides a method for preparing a lithium-ion secondary battery, comprising the following steps: providing a positive electrode plate, wherein the positive electrode plate comprises a positive electrode active material and a positive electrode lithium supplement material, wherein the positive electrode lithium supplement material comprises a lithium-rich metal oxide, wherein the lithium-rich metal oxide contains one or more elements of Ni, Co, Fe, Mn, and Cu; providing an electrolyte, wherein the electrolyte comprises an electrolyte lithium salt and a solvent, and the total mass of the fluorine element in the anions of the electrolyte lithium salt accounts for ε<14% of the total mass of the electrolyte, and optionally, 1.5%≤ε≤9.5%; assembling the positive electrode plate, the negative electrode plate, and the electrolyte to obtain a lithium-ion secondary battery.

[0127] In some embodiments, the positive electrode sheet can be prepared by the following steps: dispersing the positive electrode active material and the positive electrode lithium supplement material and optionally the binder and optionally the conductive agent in a solvent and stirring evenly to form a positive electrode slurry; coating the positive electrode slurry on the positive electrode current collector, and drying and cold pressing to form a positive electrode active material layer. The solvent can be N-methylpyrrolidone (NMP).

[0128] In some embodiments, the step of preparing the positive electrode plate may further include: dispersing the positive electrode lithium replenishing material and optionally the binder and optionally the conductive agent in a solvent and stirring evenly to form a lithium replenishing slurry; applying the lithium replenishing slurry to the positive electrode current collector, and drying and cold pressing to form a lithium replenishing film layer. The solvent may be NMP. The lithium replenishing slurry and the positive electrode slurry may be applied simultaneously or separately. The lithium replenishing coating and the positive electrode coating may be dried simultaneously or separately, and may be cold pressed simultaneously or separately.

[0129] It is worth noting that when the step of preparing the positive electrode plate includes the step of preparing the lithium replenishing film layer, the positive electrode lithium replenishing material can be omitted in the positive electrode slurry.

[0130] The materials used in this application can be obtained through commercial channels or prepared by methods known in the art. Those skilled in the art can make appropriate choices based on the actual use environment.

[0131] In some embodiments, the positive electrode lithium supplement material can be prepared by the following method: lithium oxide and precursors of various metals are mixed and sintered in a non-oxidizing gas atmosphere to obtain lithium-rich metal oxides. The metal precursor can be selected from metal oxides, metal hydroxides, etc. The non-oxidizing gas atmosphere is, for example, an inert gas atmosphere or a nitrogen atmosphere. The sintering temperature can be 600°C to 800°C. The sintering time can be 5h to 15h, or 10h to 20h, etc.

[0132] After sintering, a crushing and classification step may be optionally included to obtain a lithium-rich metal oxide with an appropriate particle size distribution. In some embodiments, the volume average particle size D of the lithium-rich metal oxide is v 50 is 3 μm to 7 μm, optionally 3 μm to 5 μm, or 4 μm to 6 μm.

[0133] A washing step may also be optionally included after sintering. Washing away impurities on the surface of the particles through the washing step helps to improve one or more of the energy density, cycle performance and storage performance of the battery. In the washing step, anhydrous ethanol may be used for washing. The washing time may be 0.5h to 1h. After washing, the particles are dried. The drying temperature may be 80°C to 200°C, for example, 120°C to 160°C. The drying time may be 5h to 15h, for example, 8h to 12h. In some embodiments, the washing step is performed after the crushing and grading step. This helps to more fully wash away impurities and improve the purity of the lithium-rich metal oxide.

[0134] Li2Cu x1 Ni 1-x1-y1 M y1 O2 is taken as an example to illustrate the preparation method:

[0135] S1: Weigh Li2O, NiO, CuO and optional oxide powders of metal M, and mix them evenly by ball milling. In S1, Li2O can be appropriately excessive. For example, in the mixed powder, the ratio of the molar content of Li to the total molar content of metal elements other than Li is 2:05:1 to 2.12:1. As an example, in the mixed powder, the molar ratio of Li, Ni, and Cu elements is 2.05:0.4:0.6.

[0136] S2: Sintering the mixed powder in a non-oxidizing gas atmosphere (e.g., a nitrogen atmosphere). In S2, the sintering temperature can be 600°C to 800°C, optionally 650°C to 750°C. The sintering time can be 5h to 15h, optionally 8h to 10h. After the sintering is completed, naturally cool to room temperature to obtain a lithium-rich metal oxide. The sintered product can also be subjected to subsequent crushing and grading steps and / or washing steps to obtain a lithium-rich metal oxide.

[0137] In some embodiments, the temperature may be raised to the sintering temperature at a heating rate of 1°C / min to 10°C / min. Alternatively, the heating rate is 1°C / min to 5°C / min, 3°C / min to 8°C / min, or 3°C / min to 5°C / min.

[0138] S3: crush and classify the sintered product to obtain a classified product. In S3, the volume average particle size D of the classified product is v 50 may be 3 μm to 7 μm, further may be 3 μm to 5 μm, or 4 μm to 6 μm.

[0139] S4: washing the classified product and drying it to obtain a lithium-rich metal oxide final product. In S4, anhydrous ethanol may be used for washing. The washing time may be 0.5 h to 1 h. The drying temperature may be 80° C. to 200° C., for example, 120° C. to 160° C.

[0140] In addition to the preparation method of the positive electrode sheet of the present application, other structures and preparation methods of the lithium-ion secondary battery of the present application are well known. For example, the negative electrode sheet can be prepared as follows: the negative electrode active material and the optional conductive agent and the optional binder are dispersed in a solvent (such as NMP or deionized water), stirred evenly and then coated on the negative electrode current collector, and dried and cold pressed to obtain the negative electrode sheet.

[0141] In some embodiments, the positive electrode sheet, the isolation membrane, and the negative electrode sheet can be formed into an electrode assembly through a winding process or a lamination process; the electrode assembly is placed in an outer package, injected with electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion secondary battery.

[0142] The optional technical features of the lithium-ion secondary battery of the present application are also applicable to the preparation method of the present application.

[0143] Device

[0144] The present application also provides a device, the device comprising at least one of the lithium-ion secondary battery, battery module, or battery pack of the present application. The lithium-ion secondary battery, battery module, or battery pack can be used as a power source for the device, or as an energy storage unit for the device. Examples of devices may include, but are not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0145] The device can select a lithium-ion secondary battery, a battery module or a battery pack according to its use requirements.

[0146] Figure 6 This is an example device. The device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. The device can use a battery pack or a battery module according to actual use requirements.

[0147] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a lithium-ion secondary battery may be used as a power source.

[0148] Example

[0149] The following examples more specifically describe the disclosure of the present application, which are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations are possible within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0150] 1. Preparation of batteries

[0151] (I) Li2Cu cathode lithium supplement material 0.6 Ni 0.4 Preparation of O2:

[0152] (1) Weigh Li2O, NiO and CuO powders and mix them evenly by ball milling. In the mixed powder, the molar ratio of Li, Ni and Cu elements is 2.05:0.4:0.6.

[0153] (2) In a nitrogen atmosphere, the temperature is raised to 680°C at a heating rate of 3°C / min and kept at this temperature for 10 hours to sinter the mixed powder. After sintering, the temperature is naturally lowered.

[0154] (3) Crushing and classifying the sintered product to obtain D v 50 is a fractionated product of 5 μm.

[0155] (4) The fractionated product was washed with anhydrous ethanol for 0.5 h and then dried in a 160°C forced air oven for 12 h to obtain Li2Cu 0.6 Ni 0.4 O2.

[0156] Li2Cu with other Ni / Cu ratios x1 Ni 1-x1 The O2 positive electrode lithium supplement material can be prepared by referring to the above method.

[0157] (II) Preparation of positive electrode lithium supplement material Li2NiO2:

[0158] (1) Nickel-based precursor Ni(OH)2 synthesized by coprecipitation method;

[0159] (2) Precursor Ni(OH)2 and lithium oxide Li2O (purity>97%, Aldrich) were ball-milled at a molar ratio of Li / Ni=3:1 for 5 h at a rotation speed of 500 rpm to obtain a mixed powder;

[0160] (3) The mixed powder was sintered at 250°C for 2 h, 450°C for 2 h, and then heated to 700°C at a heating rate of 1°C / min and sintered for 10 h in a nitrogen atmosphere to obtain Li2NiO2.

[0161] (III) Preparation of positive electrode lithium supplement material Li5FeO4:

[0162] Lithium oxide (purity > 97%, Aldrich) and iron oxide (purity > 99%, Aldrich) were mixed evenly with a Li / Fe atomic molar ratio of 5:1, pretreated at 450°C for 8h in an argon atmosphere, then ground evenly, heated to 750°C at a rate of 5°C / min, sintered at this temperature for 18h, and finally naturally cooled to room temperature to obtain Li5FeO4 positive electrode lithium supplement material.

[0163] (IV) Preparation of positive electrode lithium supplement material Li6CoO4:

[0164] In a drying room, lithium oxide (purity > 97%, Aldrich) and cobalt oxide (purity > 99%, Aldrich) were ball-milled for 12 hours at a Li / Co atomic molar ratio of 6:1. After mixing evenly, they were heated at 700°C for 12 hours under an argon atmosphere and finally naturally cooled to room temperature to obtain Li6CoO4 positive electrode lithium supplement material.

[0165] (V) Preparation of lithium-ion secondary batteries

[0166] Example 1

[0167] Preparation of positive electrode

[0168] The positive electrode active material LiFePO4 (abbreviated as LFP), the conductive agent acetylene black, the binder polyvinylidene fluoride (PVDF), the positive electrode lithium supplement material Li2Cu x1 Ni 1-x1 O2 (x1 = 0.6) was mixed in a solvent NMP in a weight ratio of (98 × 0.97) : (98 × 0.01) : (98 × 0.02) : 2, and stirred to obtain a positive electrode slurry. The positive electrode slurry was applied to the two opposite surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained. The surface density of the positive electrode active material layer was 19.5 mg / cm 2 , compacted density is 2.4g / cm 3 .

[0169] Preparation of negative electrode

[0170] The negative electrode active material artificial graphite, the conductive agent acetylene black, the binder styrene butadiene rubber (SBR) and the thickener sodium carboxymethyl cellulose (CMC-Na) were dispersed in the solvent deionized water according to a weight ratio of 96.5:0.7:1.8:1, and the negative electrode slurry was obtained after being fully stirred and mixed. The negative electrode slurry was coated on the two opposite surfaces of the negative electrode current collector copper foil, and after drying and cold pressing, the negative electrode sheet was obtained. Among them, the surface density of the negative electrode active material layer is 9.7mg / cm 2 , compacted density is 1.7g / cm 3 .

[0171] Preparation of electrolyte

[0172] Ethylene carbonate EC and ethyl methyl carbonate EMC are mixed evenly in a volume ratio of 3:7 to obtain a solvent; then electrolyte lithium salts LiTFSI and LiDFOP are dissolved in the above solvent and mixed evenly to obtain an electrolyte. The concentration of LiTFSI in the electrolyte is 0.8M (mol / L), and the concentration of LiDFOP is 0.2M.

[0173] Preparation of lithium-ion secondary batteries

[0174] The positive electrode sheet, the polyethylene PE / polypropylene PP porous composite isolation membrane, and the negative electrode sheet are stacked in order, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, injected with electrolyte and packaged to obtain a lithium-ion secondary battery.

[0175] Examples 2 to 27 and Comparative Examples 1 to 2

[0176] The preparation of the lithium-ion secondary battery is similar to that of Example 1, except that the relevant preparation parameters of the positive electrode plate and the electrolyte are adjusted, as shown in Table 1. In Example 27, the positive electrode lithium supplement material is provided on the surface of the positive electrode active material layer away from the positive electrode current collector in the form of a lithium supplement film layer. The lithium supplement film layer uses PVDF as a binder.

[0177] Examples 28 to 48 and Comparative Examples 3 to 4

[0178] The preparation of the lithium-ion secondary battery is similar to that of Example 1, except that the preparation parameters of the positive electrode sheet and the electrolyte are adjusted, wherein the positive electrode active material is LiNi 0.5 Co 0.2 Mn 0.3 O2 (abbreviated as NCM523); the surface density of the positive electrode active material layer is 18 mg / cm 2 , compacted density is 3.4g / cm 3 ; The surface density of the negative electrode active material layer is 10.7 mg / cm 2 , compacted density is 1.7g / cm 3 ; The other parameters are detailed in Table 3. And, in Example 48, the positive electrode lithium supplement material is in the form of a lithium supplement film layer disposed on the surface of the positive electrode active material layer away from the positive electrode current collector. The lithium supplement film layer uses PVDF as a binder.

[0179] In Tables 1 and 3, the free lithium mass percentage refers to the mass percentage in the lithium-rich metal oxide. The positive electrode lithium supplement material content refers to the mass percentage in the positive electrode active material layer. The fluorine percentage ε refers to the total mass of the fluorine element in the anion of the electrolyte lithium salt in the electrolyte relative to the total mass of the electrolyte.

[0180] 2. Battery performance test:

[0181] 1. Take the electrolyte sample before injection into the battery and test the fluorine content ε using the method described above.

[0182] 2. First charge and discharge specific capacity test

[0183] At room temperature (25°C), charge the battery at a constant current of 1C to the charge termination voltage (4.25V for LFP battery and 4.35V for NCM battery), then charge at a constant voltage to a current of 0.05C, and record the charge capacity at this time, which is the charge capacity of the first cycle; then discharge at a constant current of 1C to the discharge termination voltage (2.5V for LFP battery and 2.8V for NCM battery), and record the discharge capacity at this time, which is the discharge capacity of the first cycle.

[0184] First charge specific capacity (mAh / g) = first cycle charge capacity / positive electrode active material mass

[0185] First discharge specific capacity (mAh / g) = 1st cycle discharge capacity / positive electrode active material mass

[0186] 3. High temperature cycle performance test

[0187] At 45°C, charge the battery at a constant current of 1C to the charge termination voltage, then charge at a constant voltage to a current of 0.05C; then discharge at a constant current of 1C to the discharge termination voltage, and then let it stand for 5 minutes. This is a cycle charge and discharge process. Record the discharge capacity at this time, which is the discharge capacity of the first cycle. Perform a cycle charge and discharge test on the battery according to the above method, and record the discharge capacity of each cycle.

[0188] Battery cycle capacity retention rate at cycle X (%) = discharge capacity at cycle X / discharge capacity at cycle 1 × 100%

[0189] 4. Test of metal ion deposition on negative electrode

[0190] The battery after the high temperature cycle performance test 3 is disassembled, and the negative electrode plate is taken out; the negative electrode active material layer of the negative electrode plate is peeled off, and 2 g of the negative electrode active material layer is added to an acid solution (such as aqua regia) for digestion. The digestion can be carried out under stirring (such as mechanical stirring or microwave stirring, etc.), and the digestion time can be 30 minutes; the digested solution is added to the ICAP 7400 spectrometer to quantitatively analyze the metal ion deposition amount of the negative electrode plate.

[0191] 5. Overcharge performance test

[0192] a) Fully charge the battery: At room temperature (25°C), charge the battery at a constant current rate of 1C to the charge termination voltage, and then charge at a constant voltage to a current of 0.05C. At this time, the battery is fully charged (100% SOC).

[0193] b) Charge the fully charged battery at a constant current rate of 1C until the battery fails (the battery failure standard can refer to the EUCAR battery abuse standard level. When the battery reaches HL3 level (the battery starts to smoke) or above, it is considered to be failed), then stop charging. Record the battery's SOC at this time.

[0194] 6. High temperature safety performance test

[0195] The test can be carried out according to GB / T 31485-2015 standard. The specific steps are:

[0196] a) Fully charge the battery according to the method in Test 4 step a).

[0197] b) Place the fully charged NCM positive electrode battery in a hot box (for LFP positive electrode batteries, use heating plates on all sides), and heat to 80°C at a heating rate of 5°C / min; then heat the hot box by 5°C at a rate of 5°C / min and keep warm for 30 minutes; if the battery has not failed, continue to heat and keep warm in the above manner until the battery fails (the battery failure standard can refer to the EUCAR battery abuse standard level, and the battery is judged to have failed when it reaches HL3 level (the battery starts to smoke)). Record the temperature of the hot box when the battery fails. The higher the failure temperature, the better the high-temperature safety performance of the battery. You can also record the highest temperature reached after the battery fails as needed. The lower the highest temperature reached after the battery fails, the better the high-temperature safety performance of the battery.

[0198] 7. High temperature storage performance test

[0199] Take 5 batteries of each type, charge them at room temperature (25°C) at a constant current rate of 1C to the charge termination voltage, and then charge them at a constant voltage to 0.05C; then discharge them at a constant current rate of 1C to the discharge termination voltage, and measure the discharge capacity as E0. Then place the fully charged batteries in a 60°C oven for 30 days; then take out the batteries and immediately test their discharge capacity at room temperature (25°C) and record it as E0. n .

[0200] The capacity retention rate of the battery after storage at 60°C for 30 days = (E n -E0) / E0×100%. Take the average value of the high temperature storage capacity retention rate of the five batteries.

[0201] In the above tests 3-7, the charging end voltage of LiFePO4 battery is 3.65V, and the discharging end voltage is 2.5V; 0.5 Co 0.2 Mn 0.3 The charge termination voltage of the O2 battery is 4.35V and the discharge termination voltage is 2.8V.

[0202] The batteries of Examples 1 to 27 and Comparative Examples 1 to 2 are referred to as LFP batteries, and the test results are shown in Table 2. The batteries of Examples 28 to 48 and Comparative Examples 3 to 4 are referred to as NCM batteries, and the test results are shown in Table 4.

[0203] Table 1: LFP battery preparation parameters

[0204]

[0205] Table 2: LFP battery test results

[0206]

[0207] It can be seen from the data of Examples 1 to 13 and Comparative Examples 1 to 2 that by adding a lithium-rich metal oxide as a positive electrode lithium supplement material to the positive electrode active material layer of the LFP battery, and the lithium-rich metal oxide contains one or more elements of Ni, Co, Fe, Mn, and Cu, and the electrolyte satisfies ε < 14%, it can effectively compensate for the active lithium consumed by SEI film formation and side reactions, and the battery has less metal ion dissolution. Therefore, the LFP battery can obtain a higher initial discharge capacity, high-temperature cycle performance, and high-temperature storage performance, while the failure temperature of the battery in the high-temperature safety test is significantly improved, so that a higher high-temperature safety performance is also obtained. In addition, the maximum temperature reached by the battery after thermal failure is also significantly reduced, further indicating that it has improved high-temperature safety performance.

[0208] In Comparative Example 1, no positive electrode lithium replenishing material is added, and the fluorine content of the anion of the electrolyte lithium salt in the electrolyte is relatively high, resulting in low initial discharge capacity, high-temperature cycle performance and high-temperature storage performance of the battery, and the failure temperature of the battery in the high-temperature safety test is low, and the temperature reached after failure is high, so the high-temperature safety performance is poor.

[0209] In Comparative Example 2, positive electrode lithium replenishing material is added. Although the initial discharge capacity, high temperature cycle performance and high temperature storage performance of the battery are improved, due to the high fluorine content of the anion of the electrolyte lithium salt in the electrolyte, the metal dissolution phenomenon of the positive electrode lithium replenishing material is aggravated, so that the high temperature safety performance of the battery is still poor.

[0210] It can be seen from the results of Examples 11 and 14 to 19 that adding an appropriate amount of positive electrode lithium supplement material to the positive electrode active material layer enables the battery to have higher high temperature safety performance while also taking into account higher initial discharge capacity, high temperature cycle performance and high temperature storage performance. In addition, increasing the amount of positive electrode lithium supplement material added can further improve the overcharge performance of the battery.

[0211] It can be seen from the results of Examples 11, 20 to 23 that the positive electrode lithium supplement material Li2Cu x1 Ni 1-x1-y1 M y1 In O2, when the Ni / Cu atomic ratio is within an appropriate range, the battery's initial discharge capacity can be improved, as well as its high-temperature cycle performance and high-temperature storage performance.

[0212] Table 3: NCM battery preparation parameters

[0213]

[0214] Table 4: NCM battery test results

[0215]

[0216] From the comparison of Examples 28 to 40 and Comparative Examples 3 to 4, it can be seen that by adding lithium-rich metal oxide as a positive electrode lithium supplement material to the positive electrode active material layer of the NCM battery, and the lithium-rich metal oxide contains one or more elements of Ni, Co, Fe, Mn, and Cu, and the electrolyte satisfies ε < 14%, the battery can have a higher initial discharge capacity while significantly improving the failure temperature of the battery in a high temperature environment, so that the battery has a higher high temperature safety performance. In addition, the amount of metal ions dissolved in the battery is significantly reduced, which is also beneficial to improving the initial discharge capacity of the battery, while enabling the battery to obtain higher high temperature cycle performance and high temperature storage performance.

[0217] In Comparative Example 3, no positive electrode lithium replenishing material is added, and the fluorine content of the anion of the electrolyte lithium salt in the electrolyte is relatively high, resulting in low high-temperature cycle performance and high-temperature storage performance of the battery, and the failure temperature of the battery in the high-temperature safety test is low, so the high-temperature safety performance is poor.

[0218] In Comparative Example 4, positive electrode lithium replenishing material is added. Although the high temperature cycle performance and high temperature storage performance of the battery are improved, the high fluorine content of the anion of the electrolyte lithium salt in the electrolyte is high, which aggravates the metal dissolution phenomenon of the positive electrode lithium replenishing material, making the high temperature safety performance of the battery still poor.

[0219] It can be seen from the results of Examples 38, 41 to 44 that the positive electrode lithium supplement material Li2Cu x1 Ni 1-x1-y1 M y1 In O2, when the Ni / Cu atomic ratio is within an appropriate range, the battery's initial discharge capacity can be improved, as well as its high-temperature cycle performance and high-temperature storage performance.

[0220] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A lithium-ion secondary battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein: The positive electrode plate comprises a positive electrode active material and a positive electrode lithium supplement material, wherein the positive electrode lithium supplement material comprises a lithium-rich metal oxide, and the lithium-rich metal oxide is selected from Li x M 1 O 0.5(2+x) 、Li2M 3 O4、Li3M 4 O4、Li5M 5 O4、Li5M 6 O6, one or more, where x≥1, M 1 One or more selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, M 3 One or more selected from Ni, Co, Fe, Mn, Sn, Cr, V, Nb, M 4 One or more selected from Ni, Co, Fe, Mn, Sn, Cr, V, Mo, Nb, M 5 One or more selected from Ni, Co, Fe, Mn, Sn, Cr, Mo, M 6 One or more selected from Ni, Co, and Mn, M 1 、M 3 、M 4 、M 5 、M 6 The valence state of each element in is lower than its own highest oxidation state; The electrolyte comprises an electrolyte lithium salt and a solvent, wherein the electrolyte lithium salt is selected from a combination of LiPF6 and an organic lithium salt, LiBF4, a combination of LiBF4 and an organic lithium salt, and one or more of an organic lithium salt, and the organic lithium salt is selected from lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorophosphate, lithium difluorobisoxalatophosphate, lithium tetrafluorooxalatophosphate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, di(trifluoromethylsulfonyl)methyl lithium, and tri(trifluoromethylsulfonyl)methyl lithium. The concentration of LiPF6 in the electrolyte is 0 to 0.4 mol / L, and the total mass of fluorine element in the anions of the electrolyte lithium salt relative to the total mass of the electrolyte satisfies the following ratio: ε≥0.5% and ε<14%.

2. The lithium ion secondary battery according to claim 1, wherein 1.5%≤ε≤9.5%.

3. The lithium ion secondary battery according to claim 2, wherein: 2%≤ε≤9.3%.

4. The lithium ion secondary battery according to claim 3, wherein: 2.5%≤ε≤9.2%.

5. The lithium ion secondary battery according to claim 1, wherein The lithium-rich metal oxides include Li2MnO2, Li5FeO4, Li6CoO4, Li2NiO2, Li2Cu x1 Ni 1-x1-y1 M y1 O2, and optionally including one or more of Li3VO4, Li3NbO4, wherein 0<x1≤1, 0≤y1<0.1, M is selected from one or more of Zn, Sn, Mg, Fe and Mn.

6. The lithium ion secondary battery according to claim 5, wherein: 0.2≤x1≤0.8。 7. The lithium ion secondary battery according to claim 6, wherein: 0.4≤x1≤0.6。 8. The lithium ion secondary battery according to claim 1, wherein The lithium-rich metal oxide contains free lithium, and the free lithium includes one or more of LiOH, LiHCO3 and Li2CO3, and the mass proportion of the free lithium in the lithium-rich metal oxide is ω≤5wt%.

9. The lithium ion secondary battery according to claim 8, wherein: ω≤3wt%.

10. The lithium ion secondary battery according to claim 9, wherein 0.3wt%≤ω≤0.7wt%.

11. The lithium ion secondary battery according to claim 1, wherein At least a portion of the outer surface of the lithium-rich metal oxide has a coating layer, and the coating layer includes one or more of metal fluorides, oxides, metal phosphates, carbon materials, and conductive polymers.

12. The lithium ion secondary battery according to claim 11, wherein The metal fluoride is selected from AlF3; the oxide is selected from one or more of V2O5, Al2O3, ZrO2, TiO2, ZnO, SiO2, and B2O3; the metal phosphate is selected from one or more of AlPO4, FePO4, Co3(PO4)2, and Ni3(PO4)2.

13. The lithium ion secondary battery according to claim 1, wherein The electrolyte lithium salt is selected from LiBF4, a combination of LiBF4 and an organic lithium salt, and one or more of the organic lithium salts.

14. The lithium ion secondary battery according to claim 1, wherein The electrolyte lithium salt is selected from organic lithium salts.

15. The lithium ion secondary battery according to claim 14, wherein: The electrolyte lithium salt includes one or more of lithium bis(oxalatoborate), lithium difluorobis(oxalatophosphate), and lithium bis(fluorosulfonyl)imide.

16. The lithium ion secondary battery according to claim 1, wherein The electrolyte further satisfies that: the concentration of the electrolyte lithium salt in the electrolyte is 0.7 mol / L to 4 mol / L.

17. The lithium ion secondary battery according to claim 16, wherein: The electrolyte further satisfies that: the concentration of the electrolyte lithium salt in the electrolyte is 0.7 mol / L to 3 mol / L.

18. The lithium ion secondary battery according to claim 1, wherein The positive electrode active material is selected from Li z CoO2、Li z NiO2、Li z MnO2、Li z Mn2O4、Li z Ni a Co b Mn c M' d O2、Li z Ni 1-u Co u O2、Li z Co 1-u Mn u O2、Li z Ni 1-u Mn u O2、Li z Ni α Co β Mn γ O4、Li z Mn 2-η Ni η O4、Li z Mn 2-η Co η O4、Li z FePO4、Li z CoPO4、Li z MnPO4, and one or more of their modified materials, wherein M' is selected from one or more of Al, Mo, Nd, and Zn, z independently satisfies 0.5≤z≤1.3, 0<a<1, 0<b<1, 0<c<1, 0≤d<1, a+b+c+d=1, u independently satisfies 0<u<1, 0<α<2, 0<β<2, 0<γ<2, α+β+γ=2, and η independently satisfies 0<η<2.

19. The lithium ion secondary battery according to claim 1, wherein: The positive electrode active material includes Li z One or more of FePO4 and its modified materials, wherein 0.5≤z≤1.

3.

20. The lithium ion secondary battery according to claim 19, wherein 0.9≤z≤1.2。 21. The lithium ion secondary battery according to claim 20, wherein: z=1。 22. The lithium ion secondary battery according to claim 19, wherein: The positive electrode active material is contained in the positive electrode active material layer of the positive electrode plate, and the surface density of the positive electrode active material layer is ≥18 mg / cm 2 .

23. The lithium ion secondary battery according to claim 22, wherein: The surface density of the positive electrode active material layer is 18 mg / cm 2 ~21mg / cm 2 .

24. The lithium ion secondary battery according to claim 1, wherein: The positive electrode active material includes Li z Ni a Co b Mn c M' d One or more of O2 and its modified materials, wherein 0.5≤z≤1.3, 0.5≤a<1, 0<b≤0.2, 0<c≤0.3, 0≤d<1, and M' is selected from one or more of Al, Mo, Nd, and Zn.

25. The lithium ion secondary battery according to claim 1, wherein: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material; wherein, The positive electrode lithium supplement material is uniformly distributed in the positive electrode active material layer, and / or, The positive electrode lithium replenishing material is disposed between the positive electrode current collector and the positive electrode active material layer in the form of a lithium replenishing film layer, and / or, The positive electrode lithium supplement material is arranged in the form of a lithium supplement film layer on the surface of the positive electrode active material layer away from the positive electrode current collector.

26. The lithium ion secondary battery according to claim 25, wherein: On at least one side of the positive electrode current collector, the mass ratio of the positive electrode active material to the positive electrode lithium supplement material is 99.9:0.1 to 85:

15.

27. The lithium ion secondary battery according to claim 26, wherein: The mass ratio of the positive electrode active material to the positive electrode lithium supplement material is 98.5:1.5 to 93:

7.

28. The lithium ion secondary battery according to claim 27, wherein: The mass ratio of the positive electrode active material to the positive electrode lithium supplement material is 98:2 to 95:

5.

29. A method for preparing a lithium ion secondary battery, comprising the following steps: A positive electrode sheet is provided, wherein the positive electrode sheet comprises a positive electrode active material and a positive electrode lithium supplement material, wherein the positive electrode lithium supplement material comprises a lithium-rich metal oxide, and the lithium-rich metal oxide is selected from Li x M 1 O 0.5(2+x) 、Li2M 3 O4、Li3M 4 O4、Li5M 5 O4、Li5M 6 O6, one or more, where x≥1, M 1 One or more selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, M 3 One or more selected from Ni, Co, Fe, Mn, Sn, Cr, V, Nb, M 4 One or more selected from Ni, Co, Fe, Mn, Sn, Cr, V, Mo, Nb, M 5 One or more selected from Ni, Co, Fe, Mn, Sn, Cr, Mo, M 6 One or more selected from Ni, Co, and Mn, M 1 、M 3 、M 4 、M 5 、M 6 The valence state of each element in is lower than its own highest oxidation state; An electrolyte is provided, the electrolyte comprising an electrolyte lithium salt and a solvent, the electrolyte lithium salt is selected from one or more of a combination of LiPF6 and an organic lithium salt, LiBF4, a combination of LiBF4 and an organic lithium salt, and an organic lithium salt, the organic lithium salt is selected from one or more of lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorophosphate, lithium difluorobisoxalatophosphate, lithium tetrafluorooxalatophosphate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, di(trifluoromethylsulfonyl)methyl lithium, and tri(trifluoromethylsulfonyl)methyl lithium, the concentration of LiPF6 in the electrolyte is 0 to 0.4 mol / L, and the total mass of fluorine element in the anions of the electrolyte lithium salt relative to the total mass of the electrolyte satisfies: ε≥0.5% and ε<14%; The positive electrode sheet, the negative electrode sheet and the electrolyte are assembled to obtain a lithium-ion secondary battery.

30. The preparation method according to claim 29, wherein: 1.5%≤ε≤9.5%.

31. A battery module, comprising the lithium ion secondary battery according to any one of claims 1 to 28 or the lithium ion secondary battery obtained according to the preparation method according to any one of claims 29 to 30.

32. A battery pack comprising the battery module according to claim 31.

33. A device comprising at least one of the lithium ion secondary battery according to any one of claims 1 to 28, the lithium ion secondary battery prepared according to any one of claims 29 to 30, the battery module according to claim 31, or the battery pack according to claim 32.

Citation Information

Patent Citations

  • Positive plate of lithium ion battery, lithium ion battery and preparation method of lithium ion battery

    CN105552344A

  • Novel secondary lithium battery electrolyte

    CN109888394A